Uso de substitutos ósseos autógenos e aloplásticos no reparo de defeitos criados em calota de coelhos: análise histomorfométrica e imunoistoquímica - Mattos, João Marcos Borges (2013)
The aim of this study was to evaluate, by histomorphometric and immunohistochemical analysis the repair of surgically created bone defects filled with blood clot, autogenous bone and carbonate-calcium phosphate cement. Ten adult male New Zealand white albino rabbits were used. Three bone defects were prepared in the right/left parietal region of each animal with an 8-mm-diameter trephine bur and filled with blood clot (Group BC), autogenous bone particulate (Group AB) and Norian® CRS® calcium phosphate-carbonate bone cement (Group CPC). The animals were euthanized 40 and 90 days postoperatively. Hematoxylin and eosin (HE)-stained sections were subjected histomorphometric analysis of the new bone formed inside the calvarial defects and sections adjacent to the H&Estained sections were used for immunohistochemical staining to determine the expression of osteocalcin (OC), osteopontin (OP) and tartrate-resistant acid phosphatase (TRAP) proteins. Histomorphometric data were analyzed statistically by ANOVA and Tukey s post hoc test at 5% significance level. At 40 days, Group AB differed significantly from the other groups with respect to the area of newly formed bone, but no significant difference was observed at 90 days. The immunohistochemical analysis revealed expression of OP, OC and TRAP proteins in all groups. In the Group AB there was a predominance of OC and OP and lower TRAP expression. The calcium phosphate-carbonate bone cement evaluated in the present study did not accelerate the protein expression dynamics during bone healing compared with the other biomaterials